(3GdTLQI GdfYeGfjIs - (3eMj GdOjf Hf YQHjs ((3QhVI GdcGXejIs)
(3ChdgG (B:s
(3eHJhQ GdChd, hChd GdehLhO efg bhdg(B: (3Yf MhGOKgG GdcGFfI ajgG HJbOjQ GdYRjR GdYdje, bGd(B: (3Ke GWdYJ Ydi GdTLQI GdhSWi(B...s
(3BNQgG (B:s
(3hGWdH GdHjGf ef WQjb JhdjO GdMQha HcSQgG hHSWgG heMVgG MJi jXgQ ecfhfgG hjJVM eUhfgG hGddg CYde HGdUhGHs
(3hjdjg TQM ddcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJUha hGdBOGH GdTQYjIs